Comparative Characteristics of the Results of Evacuation to Healthcare Facilities and Treatment Outcomes of Children Who Applied for First Aid With Acute Abdominal Pains. The Case of an Emergency Medical Setting of an Average Municipal Entity - Ekaterina А. Romanova; Leyla S. Namazova-Baranova; Elena Yu. Dyakonova; Aleksey Yu. Romanov; Kazbek S. Mezhidov; Zharadat I. Dohshukaeva (Педиатрическая фармакология, 2017)
Background. Despite the active development of diagnostic capabilities, the problems of diagnosis at the pre-hospital stage with abdominal pain remain unresolved. Objective. Our aim was to analyze the results of evacuation to healthcare facilities as well as treatment outcomes (conservative and surgical) of hospitalized children who applied for first aid with acute abdominal pain, in order to identify possible shortcomings in the existing diagnostic algorithm and its optimization. Methods. The results of treatment outcomes for children with acute abdominal pain at the pre-hospital stage and evacuation to healthcare facilities by visiting teams for the period 2014–2015. are presented by the example of the State Institution «Engels Emergency Medical Setting». Results. Difficulties in routing children to the necessary healthcare facilities (surgical or somatic) are due to the complexities of differential diagnosis of the disease in children with acute abdominal pain at the pre-hospital stage. Conclusion. The main task of the primary care and emergency physician at the pre-hospital stage, whose decision determines the direction of the diagnostic search, timeliness and adequacy of the subsequent treatment measures, is to give a correct assessment of abdominal pain syndrome.